The long noncoding RNA HORAS5 mediates castration‐resistant prostate cancer survival by activating the androgen receptor transcriptional program. Issue 5 (5th March 2019) - Parolia, Abhijit; Venalainen, Erik; Xue, Hui; Mather, Rebecca; Lin, Dong; Wu, Rebecca; Pucci, Perla; Rogalski, Jason; Evans, Joseph R.; Feng, Felix; Collins, Colin C.; Wang, Yuzhuo; et al.
Abstract : Prostate cancer (PCa) is driven by the androgen receptor (AR)‐signaling axis. Hormonal therapy often mitigates PCa progression, but a notable number of cases progress to castration‐resistant PCa (CRPC). CRPC retains AR activity and is incurable. Long noncoding RNA (lncRNA) represent an uncharted region of the transcriptome. Several lncRNA have been recently described to mediate oncogenic functions, suggesting that these molecules can be potential therapeutic targets. Here, we identified CRPC‐associated lncRNA by analyzing patient‐derived xenografts (PDXs) and clinical data. Subsequently, we characterized one of the CRPC‐promoting lncRNA, HORAS5, in vitro and in vivo . We demonstrated that HORAS5 is a stable, cytoplasmic lncRNA that promotes CRPC proliferation and survival by maintaining AR activity under androgen‐depleted conditions. Most strikingly, knockdown of HORAS5 causes a significant reduction in the expression of AR itself and oncogenic AR targets such as KIAA0101. Elevated expression of HORAS5 is also associated with worse clinical outcomes in patients. Our results from HORAS5 inhibition in in vivo models further confirm that HORAS5 is a viable therapeutic target for CRPC. Thus, we posit that HORAS5 is a novel, targetable mediator of CRPC through its essential role in the maintenance of oncogenic AR activity. Overall, this study adds to our mechanistic understanding of how lncRNA function in cancer progression. Abstract : Long non‐coding RNA (lncRNA) are novel players in cancer progression. Here, we identified a lncRNA, HORAS5, which is upregulated in castration‐resistant prostate cancer (CRPC) and is associated with worse clinical outcomes. HORAS5 promotes CRPC survival by increasing AR mRNA stability, thereby augmenting the androgen receptor transcriptional program. Knockdown of HORAS5 in vitro and in vivo attenuates proliferation and induces cell apoptosis.